Choosing Whether to Use Mobile Technology Outdoors - Trina J. Kilty (MDPI AG, 2024)
The purpose of this phenomenological study was to explore the lived experience behind the choice of whether to bring mobile technologies along while engaging in outdoor activities. Participant observer style interviews were completed in which the researcher engaged in an outdoor activity of the participants' choice while conducting interviews. How participants experience their decision not to use mobile technologies while outdoors has essences of participants' value of the outdoor experience; the relationships participants bring to the outdoors and hold with the outdoors; the tensions of work that mobile technologies bring to the outdoors; and the necessity of mobile technology to provide security. This study may help researchers understand why people choose whether to use mobile technologies while experiencing the outdoors. Designers may use the implications of these findings to leverage the perceived benefits to develop technology-enhanced applications for meaningful learning. By understanding how people experience mobile technologies outdoors, designers could develop applications for mobile devices that people value, use, and learn from while outdoors.